Decoupling Urban Car Use and Metropolitan GDP Growth - Kenworthy, Jeff (Eco-Logica Ltd, 2013)
Data for 1995 and 2005 on forty-two cities in the USA, Canada, Australia, Europe and Asia suggest that car use as well as total motorised mobility have decoupled from real growth in metropolitan GDPs. The car vehicle kilometres travelled per unit of GDP in thirty-nine out of the forty-two cities studied has reduced by an average of 24%. In thirty-five or 83% of the cities, total motorised passenger kilometres travelled per unit of GDP was lower in 2005 than it was in 1995, by an average of 26%. Decoupling of urban mobility from GDP can occur in the context of still rising car use or total mobility. However, in twelve out of the forty-two cities the actual car use per capita also declined by an average of over 6%. Overall, it is found that the average increase in car use in these forty-two cities from 1995 to 2005 was 7% or less than one-third of the level in the 1980s. This decoupling of car use from GDP growth is thus part of the ‘peak car use’ phenomenon. New data showing an improvement in the relative speed of public transport systems compared to general road traffic over many decades, which is being led by a strong global trend towards urban rail, may help to explain these results. Further research is needed to see if Chinese and Indian cities, with their heavy investments in rail, can also start to show a decoupling of passenger transport from GDP. Overall, the results suggest a possible future where wealth can continue to be created globally whilst reducing the use of cars, oil and their damaging global impacts.